Public Relations Writing: Strategies & Structures, 11th Edition - Doug Newsom; Jim Haynes (Cengage Learning, 2016)
Combining the practical approach of a trade book with fundamental principles and theories, PUBLIC RELATIONS WRITING: STRATEGIES & STRUCTURES, 11th Edition, equips readers with the essential techniques and methods needed to write with understanding -- and purpose. The book thoroughly explains the different styles and techniques behind writing principles. Taking a decidedly strategic focus, the Eleventh Edition guides readers through a logical progression of PR writing. After exploring the roles and responsibilities of the PR writer, the book provides comprehensive coverage of writing principles, preparing to write, writing for select audiences and-finally-writing for crisis situations. The new edition also includes a new chapter on writing for social media, which focuses on the latest information in this changing arena. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.